Williamsella iraqiensis sp. nov., a new diatom (Bacillariophyta, Fragilariophyceae) from Sawa Lake, South Iraq - Al-Handal, Adil; Kociolek, Patrick; Abdullah, Dawood (Phytotaxa, 2016)
A new species of the genus Williamsella (Fragilariophyceae) is described from a saline lake in southern Iraq. Williamsella iraqiensis sp. nov. was found free living and as epiphyte on Chara sp. in Sawa Lake. This species is the second described of the genus Williamsella which was originally reported from Blue Lake warm springs, Utah, USA. Williamsella iraqiensis sp. nov. and W. angusta can be readily distinguished under LM by having a relatively wide sternum which results from shorter striae along valve margin. Description of valve ultrastructure and comparison with other related genera such as Fragilaria is provided. Williamsella iraqiensis is a brackish water species preferring warm waters.